2010
DOI: 10.2215/cjn.00080110
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Facility and Patient Characteristics Associated with Utilization of Home Dialysis

Abstract: Background and objectives: Nonmedical factors influencing utilization of home dialysis at the facility level are poorly quantified. Home dialysis is comparably effective and safe but less expensive to society and Medicare than in-center hemodialysis. Elimination of modifiable practice variation unrelated to medical factors could contribute to improvements in patient outcomes and use of scarce resources.Design, setting, participants, & measurements: Prevalent dialysis patient data by facility were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…HHD is more common among advantaged areas (37) in the United Kingdom and white and employed patients in the United States (12). The small number of HHD patients in our registry limits the power of our analyses and the generalizability of our results.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…HHD is more common among advantaged areas (37) in the United Kingdom and white and employed patients in the United States (12). The small number of HHD patients in our registry limits the power of our analyses and the generalizability of our results.…”
Section: Discussionmentioning
confidence: 90%
“…Prakash et al (11) found no association between area socioeconomic status (SES) and either eligibility for PD or insertion of PD catheter in Canada. HHD was associated with full-time employment and white race in the United States (12). Associations between SES and home dialysis have not been investigated in Australia, a country with comparatively high rates of home dialysis (especially HHD) (13) and universal access to health care.…”
Section: Introductionmentioning
confidence: 99%
“…Each minority group was significantly younger and had a lower prevalence of coexisting cardiovascular illnesses, factors generally associated with a greater use of home dialysis. 5,[12][13][14] Moreover, there were no meaningful differences in laboratory parameters as surrogate measures of health to explain the lower use of home dialysis. In the absence of demographic and clinical variables explaining the differential use, it is likely that these differences may arise from patient preferences, social differences (such as sufficient space at home and ability to afford the incremental expense of utilities), or factors associated with health care delivery (such as availability of predialysis nephrology care or home dialysis in communities where minorities live) or physician or provider perception of patients' ability to perform home dialysis.…”
Section: Discussionmentioning
confidence: 98%
“…Those who initiate hemodialysis (HD) face long travel times, which has been associated with worse mortality (5). Despite the importance of PD as an alternative modality in this population, PD units are increasingly consolidating to urban areas (6), rural units are less likely to offer home modalities (7), and rural units with PD programs have worse overall outcomes (8). Previous studies that examined the association of rural and micropolitan living on mortality and likelihood of kidney transplantation have had conflicting findings (9-12); most show little or no difference in outcomes compared with urban populations.…”
Section: Introductionmentioning
confidence: 99%